Intensitas dan Variasi Morfometrik Trichodina sp. pada Benih Ikan Gurami (Osphronemus gouramy Lacepede) Pendederan I yang Dijual di Pasar Ikan Purwonegoro Kabupaten Banjarnegara - Nurul Anisah; Rokhmani Rokhmani; Edy Riwidiharso (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2016)
Purwonegoro Fish Market, Banjarnegara district is the largest fish market in Central Java southern and western parts. This fish market serves as a center for buying and selling fish and fish seed traffic in a particular place to the location of the fish farmers. It will possibly spread a particular type of disease from one area to another. Trichodina sp. is found in the seed of gouramy fish hatchery center area with the pathogenicity level reached 80%. Trichodina sp. has a big role in the cultivation of gouramy production by reducing the physical condition of the fish so dangerous and cause death of gouramy in the seed phase. The results showed that as many as 150 gouramy fish fry were examined, 56 gouramy fish fry were infected Trichodina sp. All of Trichodina sp. are found as many as 573 individual from the gouramy seeds infected. Total intensity of Trichodina sp. from gouramy seeds amounted to 10.97 individual. The measurement results morphometric characters Trichodina sp. show the variation of morphometric with body diameter from 47.5 to 112.5 μm; denticle ring diameter from 22.5 to 47.5 μm; denticle diameter of 12.5 to 42.5 μm, adhesive disc diameter 37.5 to 65 μm; membrane width 2.5-7.5 μm and the number of denticle 13-28. Trichodina sp. allegedly found there are three types of T. heterodentata, T. nigra, and T. acuta.